Numerical simulation of the dynamics of the system "trolley – load – carrying rope" in a cable crane - Grigorov, O. V.; Druzhynin, E. I.; Strizhak, V. V.; Strizhak, M.; Anishchenko, G. O. (РC Tесhnology сеntеr, 2018)
We report results of research into patterns in the progress of dynamic processes and into emergence of dynamic loads when a trolley of the cable crane moves with a suspended load. These patterns could be subsequently taken into consideration when calculating actual cranes, in order to improve their reliability and durability, to avoid unfavorable events during motion of a freight trolley, as well as to define parameters of cranes of the new design. The dynamics of a cable crane is considered from the point of view of the interaction between elements of the system "trolley-load-carrying rope". We have improved a mathematical model for the system "trolley-load-carrying rope" by introducing three damping coefficients, each of which characterizes energy dissipation under different physical processes ‒ the motion of a trolley, a load, and the speed of a wind load. Numerical simulation was performed using the software package KiDyM, which at the analytical level allows the construction of motion equations for the systems that are described by a combination of ordinary differential equations. We established patterns of change in the normal and tangential inertial forces occurring during motion of the trolley along a curvilinear trajectory. Their character and magnitude were quantified. We determined dynamic characteristics of the system, taking into consideration the influence of the masses of a swinging load, a trolley, and the curvature of a rope. Emergency mode that occurs at a break of the traction rope was investigated, as well as the influence of wind load on the swinging of the load. We defined causes for the emergence of the reverse speed for a freight trolley, and the ways for its elimination. The influence of wind load on the angle of load deviation from the vertical was examined.

Наведено результати дослiджень, присвячених вивченню закономiрностей протiкання динамiчних процесiв i виникнення динамiчних навантажень при русi вiзка кабельного крана з пiдвiшеним вантажем. Данi закономiрностi в подальшому можуть бути врахованi при розрахунку реальних кранiв для пiдвищення їх надiйностi та довговiчностi, недопущення несприятливих явищ при русi вантажного вiзка, а також для визначення параметрiв кранiв нової конструкцiї. Динамiка кабельного крана розглядається з точки зору взаємодiї елементiв системи "вiзок-вантаж-несучий канат". Удосконалено математичну модель системи "вiзок-вантаж-несучий канат" шляхом введення трьох демпфуючих коефiцiєнтiв, кожен з яких характеризує розсiювання енергiї при рiзних фiзичних процесах – рух вiзка, вантажу та швидкостi вiтрового навантаження. Для чисельного моделювання використаний програмний комплекс KiDyM, який на аналiтичному рiвнi дозволяє будувати рiвняння руху систем, що описуються сукупнiстю звичайних диференцiальних рiвнянь. Отримано закономiрностi змiни нормальної i дотичної сил iнерцiї, що мають мiсце при русi вiзка по криволiнiйнiй траєкторiї. Оцiненi їх характер i величина. Визначено динамiчнi характеристики системи з урахуванням впливу мас вантажу що розгойдується, вiзка i кривизни каната. Розглянуто аварiйний режим, що виникає при обривi тягового каната i вплив вiтрового навантаження на розгойдування вантажу. Визначено причини виникнення реверсу швидкостi вантажного вiзка i шляхи його усунення. Дослiджено вплив вiтрового навантаження на кут вiдхилення вантажу вiд вертикалi.
Чисельне моделювання динаміки системи "візок – вантаж – несучий канат" кабельного крана
Keywords: cable crane; crane trolley; carrying rope; crane dynamics; numerical simulation; кабельний кран; вiзок крана; несучий канат; динамiка крана